Luke 2 : a commentary on the Gospel of Luke 9:51-19:27 - Bovon, François (Hermeneia--a critical and historical commentary on the Bible., 2013)
Bovon's magisterial commentary on the Gospel of Luke is justly renowned for its combination of judicious historical and literary treatment of the Evangelist's context and for its theological sensitivity. This volume completes the three-volume work and represents the author's careful revision and updating of the German original.